Erin go Bray. - (:unkn) unknown (Fores, S. W., 1798)
Scholarly notes may be added at a later date.
The Allied Republics of France & Ireland.
1 print : col.
Keywords: Caricatures; Cartoons; Donkey; Ireland -- Politics and government -- 1760-1820; Ireland ? History -- Rebellion of 1798; Ireland -- Relations -- France.